Cytokeratin-containing cells in proliferative diabetic retinopathy membranes. Issue 3 (March 1994) - Hiscott, P; Gray, R; Grierson, I; Gregor, Z
Abstract : Immunohistochemical techniques were used to investigate the relation between retinal pigment epithelial cells (RPE), traction retinal detachment (TRD) membranes, and combined traction rhegmatogenous retinal detachment (CTR) membranes in proliferative diabetic retinopathy. Seven CTR and five TRD membranes were obtained during closed microsurgery. Six of the seven CTR membranes and one of the five TRD membranes contained RPE. Eleven of the 12 diabetic membranes incorporated glial cells. The findings emphasise that the intravitreal membranes of proliferative diabetic retinopathy contain a diversity of cell types and indicate that RPE tend to contribute to CTR, rather than TRD, membranes. The histopathological appearance of CTR membranes is that of a hybrid between TRD and proliferative vitreo-retinopathy membranes.